Mesospheric Mountain Wave Activity in the Lee of the Southern Andes. Issue 7 (5th April 2021) - Pautet, P.‐D.; Taylor, M. J.; Fritts, D. C.; Janches, D.; Kaifler, N.; Dörnbrack, A.; Hormaechea, J. L.
Abstract: Gravity waves (GWs) generated by orographic forcing, also known as mountain waves (MWs) have been studied for decades. First measured in the troposphere, then in the stratosphere, they were only imaged at mesospheric altitude in 2008. Their characteristics have been investigated during several recent observation campaigns, but many questions remain concerning their impacts on the upper atmosphere, and the effects of the background environment on their deep propagation. An Advanced Mesospheric Temperature Mapper (AMTM) and the Southern Argentina Agile MEteor Radar (SAAMER) have been operated simultaneously during the Austral winter 2018 from Rio Grande, Argentina (53.8°S). This site is located near the tip of South America, in the lee of the Andes Mountains, a region considered the largest MW hotspot on Earth (e.g., Eckermann & Preusse, 1999; Hendricks et al., 2014; Jiang et al., 2003, 2005, 2002; Wright et al., 2016). New AMTM image data obtained during a 6‐month period show almost 100 occurrences of MW signatures penetrating into the upper mesosphere. They are visible ∼30% of time during the period corresponding to the middle of the winter season (mid‐May to mid‐July). Their intermittency is highly correlated with the zonal wind controlled by the semi‐diurnal tide, revealing the direct effect of the atmospheric background on MW penetration into the mesosphere lower thermosphere (MLT, altitude 80–100 km). Measurements of their momentum fluxes (MFs) were determined to reach very large values (average for 36 events ∼250 m 2 /s 2 ), providing strong evidence of the importance and impacts of small‐scale gravity waves at mesospheric altitudes. Key Points: Numerous mesospheric mountain waves observed in the lee of the Southern Andes, a major gravity waves hotspot, under wintertime conditions Mountain wave occurrence is highly correlated with the eastward phase of the semi‐diurnal tide in the upper mesosphere Mountain wave momentum fluxes can reach very large values, revealing their major impact on the upper atmosphere